Analysis of The Texture Profile and Sensory Quality of The Jelly with The Addition of Liquid Cork Fish (Channa striata). Issue 1 (November 2021) - Basmal, J
Abstract: Variations in the concentration of cork fish liquid in jelly were used in the investigation of the effect of cork fish liquid on the quality of jelly products. To establish the textural profile and level of preference of the panelists, the jelly was blended with the Cork fish juice. The different concentrations of Cork fish juice, such as K (0%), A (5%), B ( 10%), C (15%), and D (20%) v/v. After being mixed with Cork fish liquid according to the procedures, the jelly was packaged in plastic cups with a capacity of 50 ml each and refrigerated at a temperature of 10-15oC overnight. The purpose of this experiment was to see how cork fish juice affected the texture and sensory quality of jelly. The results reveal that panelists are willing to eat jelly mixed with Cork fish liquid, but that the more the concentration of Cork fish liquid added, the lower their preference level. Treatment A produced the best results among the cork fish liquid treatments, with a panelist preference value of 5.60, which was similar to syneresis 10.80, elasticity 0.83, cohesiveness 0.57, gumminess 419.50, elasticity 339.40, resilience 0.23, hardness 847.30, and gel strength values of 534.85 g/cm2, respectively.